Assessing Nurses' Knowledge on Medication to Reduce Errors in Iraq: Menilai Pengetahuan Perawat tentang Pengobatan untuk Mengurangi Kesalahan di Irak - Wasfi Dhahir Abid Ali; Dhuha Radhi Hashoosh; Husain Sameer Mishet; Samahir Hameed Sabri; Maher A. Atiyah (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Administering and preparing medications are fundamental aspects of nursing practice that significantly influence patient outcomes. Specific background: Medication errors during preparation or administration can lead to adverse effects, and assessing nurses' knowledge in this area is crucial for improving patient safety. Knowledge gap: Limited studies have examined the specific knowledge of nurses in Iraq, particularly in Basra hospitals, regarding these practices. Aims: This study aims to assess the knowledge of nurses in Basra Governorate hospitals concerning medication preparation and administration, identifying areas for improvement to enhance patient care. Results: The study surveyed 70 nurses (55.71% female and 44.28% male), with 47.1% holding a BSc in nursing sciences, 28.57% with a diploma, and 24.28% from secondary nursing schools. Regarding experience, 31.42% had less than one year, and 30% had 1-5 years of experience. Participants worked across emergency, internal medicine, surgery, and other departments. Nurses demonstrated a significant mean score of 1.84 in knowledge regarding drug preparation practices and a score of 1.74 in knowledge regarding drug administration, both indicating satisfactory understanding but with variability across departments. Novelty: This study provides specific data on nurses' knowledge in Basra hospitals, a region that has not been extensively studied in the context of medication management errors. Implications: These findings suggest that while nurses possess adequate knowledge of drug preparation and administration, continued education and training, especially for less experienced nurses, may further enhance patient safety. The study highlights the need for targeted interventions in Basra to address gaps in clinical practice and reduce medication errors. Highlights: Medication errors directly affect patient outcomes and treatment effectiveness. Nurses’ knowledge varies by experience and department in Basra hospitals. Continuous training improves medication safety and patient care quality. Keywords: Nursing knowledge, medication errors, drug preparation, drug administration, Basra hospitals.